EFFICIENCY AND ECONOMICS OF CONCRETE-PLASTIC-DRUM BIOGAS DIGESTER AS LOADED WITH DIFFERENT COMBINATION OF SUBSTRATES - Largo, Francis Eric C; Alama, Eduardo Z (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 18 No. 2, 2015, 2018)
Bio-digesters are implenents that convert organic matter to biogas and fertilizer (Thy et al., 2003). Waste from livestock and crops can be utilized as biogas energy. Bio-digester effluent can be applied to crops as fertilizer. Despite of its usefulness, durable and efficient designs are more affordable for commercial farms. Less costly small scale bio-digester requires frequent maintenance (SNV Netherlands, 2010). The backyard farmers demands a durable, cheap but efficient at the least level of animal population. Hence, a study was conducted in order to evaluate the efficiency, physico-chemical attributes and economic benefits of Concrete-Plastic-Drum-Biogas Digester as loaded with different combinations of substrates. The independent variables were: Treatment 1- (Swine Waste), Treatment 2- (Swine Waste + Human Waste) and Treatment 3- (Swine Waste plus Human Waste plus Giant Taro Plant). Parameters used were: 1) cooking time, 2) biogas yield, 3) volume of effluent and sludge, 4) biogas recovery efficiency, 5) savings from using the biogas instead of LPG, 6) value of effluent and sludge fertilizer, 7) Marginal Benefit Cost Ratio (MBCR), and 8) the Marginal Rate of Return (MRR). Physico-chemical characteristics of CPDBD loaded with swine waste alone (T 1 ) was considered as the best treatment. The Concrete-Plastic-Drum Biogas Digester loaded with swine manure was more efficient and effective as it recovered methane at 58% efficiency and 249 liters of biogas per day.